Benign Pheochromocytoma vs Kidney Tumor. A case presentation - Lesyibeth Rodriguez Cruzata; Aida Nelis Santiesteban Bello; Mercedes Gonzáles Garrido (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
ABSTRACT Background: Pheochromocytoma is a neuroendocrine neoplasm located in the adrenal medulla. Objective: To highlight the importance of physical examination and the detailed clinical practice, despite the new diagnostic means that are currently available. Case presentation: A 17-years-old male patient with left adrenal incidentaloma, initially classified as an abscessed renal tumor, whose surgical specimen biopsy finally showed that it corresponded to a benign pheochromocytoma it is presented. The catecholamine determination was normal, the computed tomography revealed a retroperitoneal mass that involved the left kidney and adrenal. The neoplasm was resected and he was discharged in good condition. Conclusions: Pheochromocytoma is an infrequent and complex pathology, whose surgical resolution is necessary.